2016
DOI: 10.1002/jbmr.2803
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Regulates Bone Resorption in Mice

Abstract: The circadian clock controls many behavioral and physiological processes beyond daily rhythms. Circadian dysfunction increases the risk of cancer, obesity, and cardiovascular and metabolic diseases. Although clinical studies have shown that bone resorption is controlled by circadian rhythm, as indicated by diurnal variations in bone resorption, the molecular mechanism of circadian clock-dependent bone resorption remains unknown. To clarify the role of circadian rhythm in bone resorption, aryl hydrocarbon recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 75 publications
2
62
2
Order By: Relevance
“…14 Osteoblasts can communicate with osteoclasts by excreting receptor activator of nuclear factor κ-B ligand (RANKL), which binds to its receptor RANK on osteoclasts. 19 Furthermore, genetic disruption of clock genes affects the bone phenotype in mice, [20][21][22][23][24] suggesting a causal link between circadian physiology and bone health. Another protein secreted by osteoblasts is osteoprotegerin (OPG), which binds to RANKL and prevents it from interacting with RANK, thus preventing the bone from excessive resorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Osteoblasts can communicate with osteoclasts by excreting receptor activator of nuclear factor κ-B ligand (RANKL), which binds to its receptor RANK on osteoclasts. 19 Furthermore, genetic disruption of clock genes affects the bone phenotype in mice, [20][21][22][23][24] suggesting a causal link between circadian physiology and bone health. Another protein secreted by osteoblasts is osteoprotegerin (OPG), which binds to RANKL and prevents it from interacting with RANK, thus preventing the bone from excessive resorption.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, it has been shown that circulating bone turnover markers exhibit a circadian rhythm in humans 18 and are negatively affected by a combination of circadian disruption and sleep restriction. 19 Furthermore, genetic disruption of clock genes affects the bone phenotype in mice, [20][21][22][23][24] suggesting a causal link between circadian physiology and bone health. However, it remains to be elucidated whether mistimed light exposure during shift work is causally related to skeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence demonstrate that the disturbance of the circadian clock system affects skeletal metabolism (14)(15)(16)(17). Although mice globally lacking the Bmal1 gene have been shown to exhibit decreased bone mass, which was in part explained by its deletion in osteoblastic cells (14), the lack of the Bmal1 gene in osteoclastic cells enhanced bone mass by suppressing osteoclast differentiation and activity in mice (16), indicating that the effects of the peripheral clock on bone metabolism are site and context specific, and the exact role of the molecular clock network on bone metabolism still needs to be clarified. Based on the accumulating evidence of a critical role for the intestine as a nodal organ integrating inter-organ communication through nutritional, humoral, and neuronal pathways, we hypothesized that the disruption of the circadian clock system in the intestines impairs Ca absorption and causes deleterious effects on skeletal metabolism; however, to our knowledge this scenario has not been tested so far.…”
Section: Introductionmentioning
confidence: 99%
“…The role of BMAL1 in bone remodelling processes is not limited to osteoblasts. In mice, targeted deletion of Bmal1 in osteoclasts led to the development of a high bone mass phenotype (Table 2) (Xu et al 2016). The observed reduction in bone resorption was related to the direct upregulation of Nfatc1, a master regulator of osteoclast differentiation, by the CLOCK-BMAL1 complex , Xu et al 2016.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…In mice, targeted deletion of Bmal1 in osteoclasts led to the development of a high bone mass phenotype (Table 2) (Xu et al 2016). The observed reduction in bone resorption was related to the direct upregulation of Nfatc1, a master regulator of osteoclast differentiation, by the CLOCK-BMAL1 complex , Xu et al 2016. Furthermore, it was demonstrated that expression of BMAL1 is reduced in bone marrow cells isolated from a type 2 diabetes rat model (Li et al 2018).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%